The phosphoric acid extract of fresh biochar and its compound aqueous solutions promoted tobacco plant growth by regulating nutrient-related microorganisms in rhizosphere soil - Liu, Xixi; Wang, Lifang; Li, Guowei; Xu, Chuantao; Li, Yike; Peng, Yong; Pu, Jinping; Xie, Yanfen; Chen, Yunkun; Liu, Zefan; Nian, Fuzhao; Liu, Di (Frontiers in Microbiology, 2025)
Introduction and methodsTo further explore the biochar–soil–plant interaction mechanisms, rice husk biochar and root-promoting solutions were used to prepare biochar extracts and compound aqueous solutions, to study the regulation of biochar acid extract and its compound water agent on the growth of tobacco, as well as the effects of the main nutrient content (nitrogen, phosphorus, potassium), microbial abundance, and functional diversity in the rhizosphere soil of tobacco.ResultsThe results showed that the application of different concentrations of biochar acid extract and its compound aqueous enhanced tobacco plant dry matter accumulation, improved soil pH, increased available nitrogen and organic matter, and reduced potassium and phosphorus availability. Moreover, the effect of the compound water agent treatment group on soil nutrients was greater than that of the biochar acid extract treatment group. In terms of microorganisms, the application of biochar acid extract and its compound aqueous increased the relative abundance of Sphingomonas, Vicinamibacteraceae bacterial genus, Mortierella, Penicillium fungal genus, and functional bacteria such as chemoheterotrophs, aerobic chemoheterotrophs, and saprotrophs, promoting the complexity and interconnectivity of soil microbial networks.DiscussionIn summary, the application of biochar acid extract and its compound aqueous solutions improve soil nutrients by enhancing the structure, diversity, and functional groups of the soil microbial community, thereby promoting tobacco growth. These results not only provide a theoretical basis for the interaction mechanism between biochar, soil, and tobacco, but also provide certain theoretical support for the development of biochar related fertilizers.